2012
DOI: 10.1016/j.mayocp.2012.02.029
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleus Accumbens as a Potential Target for Central Poststroke Pain

Abstract: Although deep brain stimulation (DBS) has been found to be efficacious for some chronic pain syndromes, its usefulness in patients with central poststroke pain (CPSP) has been disappointing. The most common DBS targets for pain are the periventricular gray region (PVG) and the ventralis caudalis of the thalamus. Despite the limited success of DBS for CPSP, few alternative targets have been explored. The nucleus accumbens (NAC), a limbic structure within the ventral striatum that is involved in reward and pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 41 publications
0
41
0
1
Order By: Relevance
“…The success of DBS in improving motor function in dystonia, essential tremor, and Parkinson's disease [320,321], with better stability and fewer adverse effects compared with lesioning, has opened the door for trials evaluating its efficacy in treating a host of neurologic and psychiatric disorders. There have been a number of studies evaluating DBS of the NAc for the treatment of obsessive-compulsive disorder [310,316,322], Tourette syndrome [311,323,324,325], depression [303,304,305], addiction to certain drugs of abuse, including alcohol [312,326,327,328,329], heroin [330], and nicotine [313], and central pain syndrome [331,332]. Given the known connections outlined above, it is not surprising that a recent large animal study supported the influence of NAc DBS on a variety of brain structures which could influence these and other psychiatric disorders [333].…”
Section: Surgerymentioning
confidence: 99%
“…The success of DBS in improving motor function in dystonia, essential tremor, and Parkinson's disease [320,321], with better stability and fewer adverse effects compared with lesioning, has opened the door for trials evaluating its efficacy in treating a host of neurologic and psychiatric disorders. There have been a number of studies evaluating DBS of the NAc for the treatment of obsessive-compulsive disorder [310,316,322], Tourette syndrome [311,323,324,325], depression [303,304,305], addiction to certain drugs of abuse, including alcohol [312,326,327,328,329], heroin [330], and nicotine [313], and central pain syndrome [331,332]. Given the known connections outlined above, it is not surprising that a recent large animal study supported the influence of NAc DBS on a variety of brain structures which could influence these and other psychiatric disorders [333].…”
Section: Surgerymentioning
confidence: 99%
“…However, there is no clear follow-up work on targeting the parabrachial region for DBS to alleviate chronic pain. More recently, Mallory and colleagues 124 targeted the NAcc ventral striatum in a case report of central poststroke pain, noting success when combining NAcc stimulation with commiserate PV(A)G stimulation (although they report stimulating the NAcc alone helps alleviate pain). Finally, targeting the affective components of pain, Boccard and colleagues 125 recently reported success when stimulating the anterior cingulate cortex of a patient with neuropathic pain.…”
Section: Intracranial Targetsmentioning
confidence: 99%
“…One patient achieved successful pain reduction with sole stimulation of the accompanying target [49]. Interestingly, combined implantation into the PVG and the NAcc was effective in providing complete pain relief, possibly due to inhibitory projections to the medial thalamus, the amygdala, and the PAG [68,69,70,71]. Individual patient data was not provided in the larger cohort described by Boccard et al [60] and, although they found a statistically significant VAS score decrease of 38%, the data may have been artificially elevated by excluding patients who did not achieve significant pain relief [60].…”
Section: Methodsmentioning
confidence: 99%